2013
DOI: 10.1111/jonm.12113
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personal and workplace resources on new graduate nurses' job satisfaction

Abstract: Managers should ensure empowerment structures are in place to support new graduate nurses' job satisfaction. Orientation processes and ongoing management support to build psychological capital in new graduate nurses will help create positive perceptions of the workplace, enhancing job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 51 publications
4
85
1
6
Order By: Relevance
“…According to theory of structural power in organizations, formal and informal power, access to information, opportunity for growth, support and resources can promote employee empowerment resulting in positive organizational outcomes such as job satisfaction and reduced job burnout (Gilbert, Laschinger, & Leiter, 2010;Pineau Stam, Laschinger, Regan, & Wong, 2013;Laschinger, 2008). Research has shown that nurses who felt empowered in their jobs were more committed to their organizations thereby increasing their intent to stay in their positions .…”
Section: Structural Empowermentmentioning
confidence: 99%
“…According to theory of structural power in organizations, formal and informal power, access to information, opportunity for growth, support and resources can promote employee empowerment resulting in positive organizational outcomes such as job satisfaction and reduced job burnout (Gilbert, Laschinger, & Leiter, 2010;Pineau Stam, Laschinger, Regan, & Wong, 2013;Laschinger, 2008). Research has shown that nurses who felt empowered in their jobs were more committed to their organizations thereby increasing their intent to stay in their positions .…”
Section: Structural Empowermentmentioning
confidence: 99%
“…There are several indicators that management support positively influences job satisfaction (Pineau, Spence, Regan, & Wong, 2015;Du Preez & Bendixen, 2015). Additionally, perceptions of organisational support should increase individuals' sense of self-regard and increase the likelihood of employee identification and satisfaction (Edwards & Peccei, 2015;Ugboro & Obeng, 2000).…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
“…1 Creating an empowered team is a vital nurse leadership function that can significantly influence staff morale, productivity, staff retention and associated costs, patient care, quality, and patient safety. What makes some teams succeed while others struggle?…”
mentioning
confidence: 99%